Rhythms of Recovery : Trauma, Nature, and the Body. - Korn, Leslie E. (Taylor and Francis, 2012)
Rhythm is one of the most important components of our survival and well-being. It governs the patterns of our sleep and respiration and is profoundly tied to our relationships with friends and family. But what happens when these rhythms are disrupted by traumatic events? Can balance be restored, and if so, how? What insights do eastern, natural, and modern western healing traditions have to offer, and how can practitioners put these lessons to use? Is it possible to do this in a way that's culturally sensitive, multidisciplinary, and grounded in research? Clients walk through the door with.